The Influence of Implementing Accounting Information Systems, Internal Control Systems, and Human Resource Competence on the Quality of Lumajang Regency Government Financial Reports: English - Neni Kurnia; Miqdad, Muhammad; Ika Wahyuni, Nining (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2023)
The aim of this study is to examine the eﬀect of implementing accounting information systems, internal control systems and human resource competencies on the Quality of Financial Statements in the Lumajang Regency Government. The population in this study was 65 Regional Device Work Units (SKPD) and the sample of this study was 195 respondents consisting of the ﬁnancial department, Kasubbag, & Accounting Oﬃcer at the Lumajang Regency Regional Devices Work Unit (SKPD). The sampling method uses the purposive sampling method. Hypothetical testing uses multiple linear regression analysis with the help of social package science (SPSS) statistical software Version 26. Questionnaires distributed using the Ordinal Scale measured through the Likert scale 1-5. Based on the results of the F test in this study it can be met that a signiﬁcant level of 0.000 < 0.05. That is, the application of accounting information systems, internal control systems and human resource competencies simultaneously inﬂuences the quality of ﬁnancial statements. The signiﬁcant value of the t test for the accounting information system (X1) application variable is 0.002 < 0.05, for the internal control system variable (X2) is 0.004 < 0.05 , for human resource competency variable (X3) is 0.000 < 0.05. The signiﬁcant value of the three variables < 0.05 which means that the variable has a positive and signiﬁcant eﬀect on the quality of ﬁnancial statements so that the hypotheses H1, H2 and H3 are accepted. Based on test results the hypothesis shows that if the application of an accounting information system , internal control systems and human resource competencies owned by all SKPDs in Lumajang Regency are good so the ﬁnancial statements of the Lumajang Regency Government will also be of quality in accordance with the characteristics mandated by the Regulations Government Number 71 of 2010 is relevant, reliable, comparable and understandable.